Introduction of Red Soil (Ocher) of Hormoz Island as a Natural Adsorbent to Removal of Cadmium from Aqueous Solutions - Hamed Biglari (Journal of Global Pharma Technology, 2017)
Due to teem and low cost ocher red soil in Hormoz Island (south of Iran), this study was conducted to investigate the efficiency of red soil on adsorption of cadmium from aqueous solutions. a series of steps for adsorption of cadmium on ocher were conducted which included the ocher selection/preparation, determination of chemical and physical characteristics of adsorbent, preparation of cadmium stokes, determine the equilibrium time, the effect of cadmium concentration, adsorbent dose, the effect of environmental factors (pH and temperature), and determine the adsorption kinetic and isotherm. raw ocher had better adsorption efficiency than processed type (74.33% vs. 35%), the main component of adsorbent was Fe2O3 (59.58%). The optimum conditions as dose, pH and temperature which respectively were as (20 g/L; 10; and 35 oC), the adsorption reach to 96%. The study of isotherm and kinetics showed that Cd adsorption on raw Ocher is more fitted to Freundlich isotherm and pseudo second order models. natural ocher of the island of Hormoz would be appropriate to remove the heavy metal, as no need to processing it is economical to use. As temperature has positive effect on Cd adsorption on ocher, this adsorbent can act more effective in hot climate.Keywords: Cadmium, Red soil, ocher, adsorption, Hormoz Island, aqueous solutions